Outstanding Teachers: The Steps In Acquiring Them - Aliyyah, Rusi Rusmiati; Widyasari, Widyasari; Rasmitadila, Rasmitadila; Humaira, Megan Asri; Ulfah, Sri Wahyuni; Mulyadi, Didi (International Journal for Educational and Vocational Studies, 2019)
Teachers are professional educators with the main task of educating, teaching, guiding, directing, training, evaluating, and evaluating students. So that it is expected to be able to produce graduates who are intelligent, qualified, competitive, noble and have noble character. The era of globalization requires high-quality teachers and is ready to compete, both at national, regional and international levels. The study aims to determine the criteria for outstanding teacher competitions in elementary schools by using a multi-site approach through schools that get national-level exceptional teachers in 2017 and 2018 in West Java, Banten and DKI Jakarta. Data collection techniques are carried out through interviews, documentation and observation, while data analysis techniques are used through data reduction, data display and conclusion drawing. The results of the study stated that the selection of outstanding elementary school teachers was intended to increase motivation, dedication, loyalty and professionalism of teachers who were expected to have a positive effect on improving performance and achievement. Criteria for selecting outstanding teachers consist of portfolio assessment, learning videos and teacher performance assessments, written tests consisting of teacher competencies and educational insights, scientific papers and scientific writing presentations.